Adaptive POD for power system with high wind power penetration level (2019)
"With the insertion of non-synchronous energies such as, solar and wind energy, the power systems face new challenges to maintain reliability and safety in the electric service. For this purpose, this paper proposes an adaptive supplementary controller based on a model as a reference for the improvement of damping of weak electromechanical modes. Additionally, the supplementary controller uses fuzzy logic as an adjustment mechanism for the tuning the proportional gain in the time. The methodology is tested on a proposed test system that replaces a quarter of the total installed generation for doubly fed induction generator (DFIG)-based wind farm and aggregated an external HVDC connection with 600MW. The performance of the proposed control is compared to classic control with Power Oscillation Damping (POD)."--Tomado del Formato de Documento de Grado.